Panax ginseng Polysaccharide Protected H9c2 Cardiomyocyte From Hypoxia/Reoxygenation Injury Through Regulating Mitochondrial Metabolism and RISK Pathway - Zuo, Yi-Han; Han, Quan-Bin; Dong, Geng-Ting; Yue, Rui-Qi; Ren, Xue-Cong; Liu, Jian-Xin; Liu, Liang; Luo, Pei; Zhou, Hua (Frontiers in Physiology, 2018)
Background and objective: Ischemic heart disease (IHD) has been the major issue of public health. Panax ginseng (ginseng) has been verified as an effective traditional Chinese medicines and exerted cardioprotective effect. This study aimed to investigate the polysaccharide fraction of ginseng on hypoxia/reoxygenation (H/R) injury in cardiomyocytes and the underlying mechanisms. Methods: Ginseng was extracted by ethanol and fractionated by high-speed counter current chromatography (HSCCC) and column separation. The cardioprotective effect was evaluated in H9c2 cardiomyocytes underwent H/R treatment. The cell viability, apoptosis and mitochondrial respiration were examined. Results: An acid polysaccharides fraction of ginseng (AP1) was identified the most effective fraction in protecting cardiomyocytes from H/R injury. AP1 restored the mitochondrial function by maintaining mitochondrial membrane potential (MMP), blocking the release of cytochrome C, and increasing the ATP generation and oxygen consumption rate (OCR) of cardiomyocytes. Meanwhile, AP1 induced the expression of glucocorticoid receptor (GR) and estrogen receptor (ER) which further activated reperfusion injury salvage kinase (RISK) pathway. Finally, AP1 increased nitric oxide (NO) production and regulated endothelial function by increasing endothelial NO synthase (eNOS) expression and decreasing inducible NOS (iNOS) expression in H/R injury. Conclusions: The results suggested that AP1 exerted a protective effect in myocardial H/R injury mainly through maintaining myocardial mitochondrial function, thereby inhibiting myocardial H/R caused apoptosis and increasing the expressions of GR and ER, which in turn mediated the activation of RISK pathway and eNOS-dependent mechanism to resist the reperfusion injury.